Analisis Sistem Manajemen Sekuriti: K3 dan Beban Kerja di PT. XYZ - Edy Soesanto; Farhan Saputra; Dita Puspitasari; Bayu Putra Danaya (Jurnal Riset dan Inovasi Manajemen, 2023)
This study discusses the Analysis of Security Management Systems: K3 and Workload at PT XYZ. The purpose of this study is to determine the level of work risks that have occurred to those that have not occurred at PT XYZ. By knowing the level of risk, PT XYZ's management takes policies to avoid work risks that affect operational activities and company profits. The object of this research is all employees of PT XYZ. In carrying out security management in the form of risk analysis, researchers used a five (5) scale likelihood matrix table. Then the data from the assessment results were inputted into Microsoft Excel, so that researchers could find out the risk level of each activity at PT XYZ. The number of activities used in the assessment is twelve (12) activities or jobs, starting from employees entering the company area until employees leave or leave the company area. The results of this assessment are: 1) Occupational Safety and Health (K3) has an effect on the Security Management System at PT XYZ; 2) Workload affects the Security Management System at PT XYZ; and 3) K3 and Workload affect the Security Management System at PT XYZ simultaneously.